Production of a complex nitride-containing mixture by oxidation of zirconium and aluminum in air - Ilyin A. P. Aleksandr Petrovich; An V. V. Vladimir Vilorievich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Yablunovskii G. V. (1999, 1999)
Title screen